2016
DOI: 10.1111/jai.13206
|View full text |Cite
|
Sign up to set email alerts
|

Range-wide assessment of pallid sturgeonScaphirhynchus albus(Forbes & Richardson, 1905) relative condition

Abstract: Pallid sturgeon Scaphirhynchus albus relative condition has been observed to be declining along the Nebraska reach (rkm 1212.6-801.3) of the Missouri River over the past several years; therefore, pallid sturgeon capture data was synthesized from the entire Missouri and Middle Mississippi rivers to document and compare how pallid sturgeon condition varies spatially and temporally throughout much of their current range. The study area was subdivided into four river reaches based on a priori statistical differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 24 publications
2
28
2
Order By: Relevance
“…Recent research conducted during the same period and within the same area as the present study has indicated that a large proportion of the Pallid Sturgeon population displays poor body condition (Steffensen and Mestl ; Steffensen et al. ). These factors—combined with the additive stress of fin ray removal, particularly for young Pallid Sturgeon—may have resulted in the low rate of recapture and the presumed mortality of fish examined in this study.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Recent research conducted during the same period and within the same area as the present study has indicated that a large proportion of the Pallid Sturgeon population displays poor body condition (Steffensen and Mestl ; Steffensen et al. ). These factors—combined with the additive stress of fin ray removal, particularly for young Pallid Sturgeon—may have resulted in the low rate of recapture and the presumed mortality of fish examined in this study.…”
Section: Discussionsupporting
confidence: 58%
“…As previously mentioned, pectoral fin ray abnormalities and fin ray removal may affect station-holding ability in the natural environmentor, at the very least, may require additional energy reserves to compensate for a reduction in station-holding efficiency or to overcome acute stressors caused by fin ray removal. Recent research conducted during the same period and within the same area as the present study has indicated that a large proportion of the Pallid Sturgeon population displays poor body condition (Steffensen and Mestl 2016;Steffensen et al 2017). These factors-combined with the additive stress of fin ray removal, particularly for young Pallid Sturgeon-may have resulted in the FIGURE 1.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, progeny of LMR pallid sturgeon broodstock could be stocked in the MMR. This alternative would allow managers to continue to conserve the genetic diversity of the LMR pallid sturgeon population by maximising the number of families stocked without increasing competition for resources downstream of Gavins Point Dam where food competition was identified as a potential cause of recent declines in pallid sturgeon body condition (Randall et al., ; Steffensen & Mestl, ; Steffensen, Mestl & Phelps, ). Furthermore, this option would create a refugium population to store LMR pallid sturgeon genetics, similar to the one that currently exists in the MMR for the UMR population (USFWS, ), in case of a catastrophic loss of pallid sturgeon downstream of Gavins Point Dam.…”
Section: Discussionmentioning
confidence: 99%
“…1 year in this study vs. Rotella (2017)]. Survival probability estimates of age ≥2 HRPS in this study (0.96) were similar to estimates by Rotella Year class 1 9 9 6 1 9 9 7 1 9 9 8 1 9 9 9 2 0 0 0 2 0 0 1 2 0 0 2 2 0 0 3 2 0 0 4 2 0 0 5 2 0 0 6 2 0 0 7 2 0 0 8 2 0 0 9 2 0 1 0 2 0 1 1 2 0 1 2 2 0 1 3 2 0 1 4 Gavins Point Dam where food competition was identified as a potential cause of recent declines in pallid sturgeon body condition (Randall et al, 2017;Steffensen, Mestl & Phelps, 2016). Furthermore, this option would create a refugium population to store LMR pallid sturgeon genetics, similar to the one that currently exists in the MMR for the UMR population (USFWS, 2008), in case of a catastrophic loss of pallid sturgeon downstream of Gavins Point Dam.…”
Section: Discussionmentioning
confidence: 99%
“…Karr (1981) suggested that reduced growth rates, recruitment, and condition are generally indicators of poor environmental quality. Recent observations and analyses have shown a decline in Pallid Sturgeon (Scaphirhynchus albus) condition in the upper channelized reach of the lower Missouri River (Steffensen and Mestl 2016, Steffensen et al 2017a, Randall et al 2017. This decline appears to be restricted to the reach from Gavins Point Dam (rkm 1305.1) downstream to the Kansas River confluence (rkm 591.4).…”
Section: Introductionmentioning
confidence: 99%